Recent results from E877 for Au+Au collisions at AGS energy - Braun-Munzinger, Peter; Esumi, ShinIchi; Filimonov, Kirill; Herrmann, Norbert; Stachel, Johanna; Voloshin, Sergei; Wessels, Johannes P. (Nuclear physics. A, Nuclear and hadronic physics, 2002)
The E877 experiment was dedicated to the study of hadron distributions in Au+Au collisions at the AGS. Here, we will mainly present results from the analysis of the data obtained from the last data taking run, which took place in the fall of 1995 and recorded 46 millions Au+Au events at 11.5 AGeV/c. The improved experimental apparatus and large statistics allowed to extend our previous measurements of particle flow [1-4] to K+, K−, p̄ and Λ. We will also report our latest results on two-particle correlations of like and unlike particles, as well as the measurements of double differential multiplicities of Λ-hyperons.